Effect of Coal Export on Gross Domestic Product in Indonesia - Fandy Yones Latuni; Dyah Handayani Dewi; Revi Sesario; Mohamad Ratmasa Serang; Arsad Matdoan (Budapest International Research and Critics University, 2022)
This study aims to analyze effect of coal export on gross domestic product in Indonesia. This study uses a descriptive research method with a quantitative approach. Internal secondary data is obtained through data from the Central Statistics Agency starting from 1987 to 2021 in the form of time series data. This study uses a partial test in solving the problem. The results show that coal export has a positive and significant effect on gross domestic product in Indonesia.